2021
DOI: 10.1097/meg.0000000000002274
|View full text |Cite
|
Sign up to set email alerts
|

Long-standing effect of cholecystectomy in patients with metabolic-associated fatty liver disease

Abstract: Objective The role of cholecystectomy as a risk factor in patients with metabolic-associated fatty liver disease (MAFLD) remains unclear. This study aimed to investigate if long-standing cholecystectomy is associated with advanced liver fibrosis and cirrhosis in patients with recently diagnosed MAFLD. Methods A retrospective observational study was performed in four hospitals in Mexico including patients with recently diagnosed MAFLD and a history of cholecystectomy. Subjects were divided into those with cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Furthermore, the risk of cardiovascular disease has decreased after 2 years in patients who underwent cholecystectomy, suggesting that cholecystectomy-associated elevation of cardiovascular disease risk may be ameliorated 2 years after cholecystectomy. Although there were concerns that cholecystectomy might have harmful effects in the past in metabolic indicators, such as cholesterol 12 , the results of this study suggest that there are more beneficial results.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, the risk of cardiovascular disease has decreased after 2 years in patients who underwent cholecystectomy, suggesting that cholecystectomy-associated elevation of cardiovascular disease risk may be ameliorated 2 years after cholecystectomy. Although there were concerns that cholecystectomy might have harmful effects in the past in metabolic indicators, such as cholesterol 12 , the results of this study suggest that there are more beneficial results.…”
Section: Discussionmentioning
confidence: 53%
“…Only one similar study was found. However, it employed the MAFLD definition [ 40 ]. In this study, long-standing cholecystectomy, defined as a period exceeding 6 months, patients were at risk of advanced liver fibrosis, especially when they presented an age over 50 years and dyslipidaemia.…”
Section: Discussionmentioning
confidence: 99%
“…A database from a multicentre retrospective cross-sectional study of 4 hospitals in Mexico that was performed from 2014 to 2020 was analysed for this study. This database can be found in the Harvard Dataverse [ 40 ]. These hospitals were: Medica Sur Clinic and Foundation, Central Military Hospital, General Hospital of Mexico “Dr Eduardo Liceaga” and Star Médica Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Through the analysis of previous studies and reviews, we have discussed the association between cholelithiasis and MAFLD, specifically what happens in patients who have undergone a cholecystectomy [2,[7][8][9]16,34]. Figure 3 illustrates our hypothesis about the possible roles of FXR1 and FGFR4 in MAFLD pathogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations, which occur in multiple organs such as the intestine, adipose tissue and muscle, contribute to the development of metabolic disorders, such as metabolic syndrome and MAFLD [14,15]. A recent study showed that patients with long-standing cholecystectomies (≥6 months) are at increased risk of severe liver fibrosis and cirrhosis at the time of MAFLD diagnosis, compared to patients with cholecystectomies performed recently [16]. Additionally, a meta-analysis demonstrated that cholecystectomy is associated with a 1.63 fold increase in the risk of liver disease, particularly MAFLD [12].…”
Section: Introductionmentioning
confidence: 99%